Kedah Umno, BN must overcome issue of candidates and sabotage to achieve win - Borneo Post, (KK) (Borneo Post (kk), 2012)
ALOR SETAR: Kedah Umno and Barisan Nasional (BN) must overcome the issue of candidates and sabotage if they want to win in the coming 13th general election.